HYBRYD THREATS IN TRADE AND ECONOMIC RELATIONS - Sarkisian, L.G.; Samsonova , L. V. (The actual problems of regional economy development, 2020)
The article is devoted to the study of hybrid threats in trade and economic relations, which include strengthening protectionist and neo-protectionist measures in foreign trade, gaining control over investment flows, cyber-attacks on economic and infrastructural objects of the state-object of aggression in formulating and implementing foreign economic strategy by the aggressor state. The relevance of the topic is due to the fact that in the last decade the nature of interstate conflicts has changed, which have become hybrid not only in the foreign policy sphere, but also in foreign trade. The purpose of the article is to substantiate the theoretical and methodological approaches to determining the role of hybrid threats in the formation of foreign economic policy. The approaches to defining hybrid wars and their features as undermining the foundations of national security through political, economic, informational and other instruments and providing blurring of responsibilities on the one hand, and centralized and coordinated management on the other are systematized in the article. The peculiarities of hybrid aggression in Ukraine by the Russian Federation are determined, and its main manifestations in the foreign economic sphere are analyzed. The directions of hybrid threats realization in trade and economic relations are identified. The main types of trade restrictions that were used by the Russian Federation to increase the level of vulnerability of the economic system of Ukraine are studied. A critical analysis of trade interventions, including: tariff and non-tariff (anti-dumping measures, subsidies, phytosanitary requirements, etc.) restrictions, sanctions, financial measures, protection of intellectual property rights and others is made. A timely and balanced foreign economic policy is reasonable to adopt for countering hybrid threats. The policy needs to be in line with the overall government strategy, and can therefore significantly mitigate and / or avoid the effects of aggressive action.